Children's Education Based on the Qur'an and Hadith: A Literature Review - Mardiyah Mardiyah; Abu Anwar; Abdul Wahab (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2026)
Child education based on the Qur'an serves as a fundamental foundation for developing character, spirituality, and holistic intelligence from an early age. This study aims to examine and formulate a Qur'an-based early childhood education model to strengthen Islamic character in response to the challenges of the digital era. Using a library research method with a descriptive-analytical approach, the study analyzes Qur'anic verses, Hadith, classical and contemporary Qur'anic exegesis, and Islamic education literature. The findings indicate that Qur'an- and Hadith-based child education emphasizes faith formation, moral habituation, and balanced development of cognitive, affective, and psychomotor aspects. This educational model is relevant in addressing moral crises and value disorientation in modern education.The findings indicate that a Qur'an- and Hadith-based child education model encompasses three main pillars:(1) Habituation (Value Inculcation): the cultivation of manners and moral conduct through Qur'anic narratives;(2) Understanding (Islamic Cognition): the introduction of fundamental concepts of creed (ʿaqīdah), Islamic law (sharīʿah), and worship through simple translations and interpretations; and (3) Practice (Internalization): the daily practice of acts of worship such as prayer and fasting, supported by age-appropriate guidance. Overall, the study demonstrates that the Qur'an and Hadith provide a comprehensive framework for child education through the inculcation oftawḥīd, the habituation of noble character, the development of intellect, and the balanced integration of cognitive, affective, and psychomotor domains. Qur'an- and Hadith-based child education is therefore highly relevant in addressing the moral crisis and value disorientation prevalent in modern educational systems.